Honouring a love of books and reading in library and information science - Rothbauer, Paulette; Harrington, Marni (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
This paper presents the findings of a research study into the “love of books” trope in Library and Information Science. Semi-structured interviews were conducted with 23 MLIS students in Winter and Summer terms of 2019. Interview questions were designed to elicit motivations for entering the field and taking the degree. The study findings show that students’ decisions are animated by a love of books and reading, a love of libraries, and by a desire to work with and serve others. We argue that by putting love and desire at the centre of analysis the findings can be understand as positive affective engagement with information, information processes, information institutions, and information practices.